Community Based Nursing Intervention Strategies and its effectiveness on Alcohol Dependence and Quality of Life among Alcoholics - Selvam S, Dinesh (Journal of Neonatal Surgery, 2025)
Alcoholism or alcohol dependence is a serious problem that needs to be recognized and addressed in India at the individual, medical and social levels. There is a need to develop comprehensive, integrated and people-centered alcohol control and prevention programs. This study utilizes the community resources, brings the importance of community participation through community forums, community camps, group discussions, community mapping, and diagnoses the nursing problems in alcohol dependence. Comprehensive, coordinated interventions with involvement of the community were developed and implemented for alcohol dependents. The community based nursing interventions were Individual need- based nursing interventions, Alcohol Education, Family counselling, Detoxification and Training of local workers. The overall mean difference in the score of level of dependence and quality of life was statistically significant revealing the effectiveness of the intervention. The individual based alcoholic education, nursing interventions based on the individual need and family counseling proved to be effective. Community volunteers provided support in identification and motivating the alcoholics for the interventions. There was a high correlation between the level of dependence and quality of life among alcoholics. This revealed that the Quality of life among alcoholics is directly related to the level of their dependence on alcohol.